Fishing for Litter: Creating an Economic Market for Marine Plastics in a Sustainable Fisheries Model - Nguyen, Linh; Brouwer, Roy (Frontiers in Marine Science, 2022)
This paper studies an economy specialized in fisheries facing a rising marine litter problem. We present a dynamic optimization model to explain the mechanism through which marine litter causes inefficiencies in the fishery sector. We do so by investigating the properties of the model when the marine litter externality is internalized through the price of fish. We find that if the marine litter externality is neglected, fish harvest increases and ocean quality deteriorates. We subsequently explore the possibility of introducing an incentive scheme where marine litter can be traded in a hypothetical market. The introduction of a so-called fishing-for-litter market removes the inefficiencies caused by fishermen neglecting marine litter and provides a direct incentive for them to maximize overall welfare through resource recovery, i.e. by converting plastic waste into a new valuable resource.